Designing VxNbMoTa refractory high-entropy alloys with improved properties for high-temperature applications. (15th January 2021) - Wang, M.; Ma, Z.L.; Xu, Z.Q.; Cheng, X.W.
Abstract: Poor high/medium-temperature phase stability and/or low room-temperature ductility are currently bottlenecks of refractory high-entropy alloys (RHEAs) that restrict their high-temperature applications. Here, we explored novel V x NbMoTa RHEAs with vanadium concentrations of 0–25 at.%. V x NbMoTa RHEAs exhibit a single body-centered cubic (BCC) structure with unprecedented phase stability at a wide temperature range from solidus down to 350°C. The grain structure of V x NbMoTa can be substantially refined when increasing the V concentration since higher V contents induce stronger solutal effects which contribute to higher growth restriction factors. Equimolar VNbMoTa exhibits the yield strength of 811 MPa at 1000°C that is superior to most RHEAs reported by far, and this alloy also shows excellent room-temperature ductility with the fracture strain > 25% and no strain-softening at high temperature, which is rarely seen in many popular RHEAs. These exceptional performances of VNbMoTa enable it to be a very promising material for high-temperature applications. Graphical nAbstract: Image, graphical abstract